Armed Conflicts and (De)Peasantization in the Life Courses of Today's Youths in the South of Bolivar, Colombia - Ocampo Talero, Ángelica; Ferro Medina, Juan Guillermo; Jaramillo Gómez, Olga; Guerrero Díaz, Alba; Tobón Quintero, Gabriel; Aguilar, Irene Giovanni (Última Década, 2023)
The article is the result of a collaborative research work carried out with young and adult people from Colombian peasant communities, as a contribution for the Commission for the Clarification of Truth, Coexistence and Non-Repetition (CEV). It proposes a perspective of the armed conflict through the analysis of the generational positions of today’s youths within the context of the socio-political codes of their life courses. It presents the effects of depeasantization from a war on youth, showing the generation legacies that they are carrying up to today. As a conclusion, the article states the challenges that these results suggest in order to make territorial peace to be feasible.